Efektivitas dan Efisiensi Pengelolaan Keuangan Daerah - Andri Meiriki; Adi Musharianto; Novitri Landong NS (Department of State Administration - Musamus University, 2020)
The present study was aimed at examining the effectiveness and efficiency of the financial management of South Tangerang City, Banten Province. The present study was categorized as a descriptive study. This study emphasized more on secondary data analysis. The data used in the present study were institutional administrative data (i.e., the data from South Tangerang City Government) comprising the Regional Budget of South Tangerang and the 2014-2018 Report on the Regional Government Administration (LPPD), as well as the regional financial budget stated in the report issued by South Tangerang Statistics. The instruments of analysis used in the study were effectiveness ratio and efficiency ratio. The study found that the financial management of South Tangerang City was categorized as highly effective. Further, the study also found that the financial management of South Tangerang City was categorized as fairly efficient.